Baryonic spindles from conifolds - Minwoo Suh (Journal of High Energy Physics)
Abstract We construct supersymmetric AdS 3 × Σ solutions with baryonic charge in the Betti-vector truncation of five-dimensional gauged N $$ \mathcal{N} $$ = 4 supergravity where Σ is a spindle. The truncation is obtained from type IIB supergravity on AdS 5 × T 1,1. The solutions realize supersymmetry by the anti-twist. The dual field theories are 2d N $$ \mathcal{N} $$ = (0, 2) SCFTs from the Klebanov-Witten theory compactified on a spindle. We calculate the holographic central charge of the solutions and it precisely matches the result from the gravitational block.